Penerapan metode pembelajaran PPKn dalam meningkatkan minat belajar siswa di SMP Negeri 3 Imogiri - Aprita, Marsela; Kurnia, Heri; Wahono, Joko (Universitas Cokroaminoto Yogyakarta, 2023)
The research entitled Application of Civics Learning Methods in Increasing Students' Learning Interest at SMPN 3 Imogiri aims to find out how the application of Civics learning methods can increase students' interest in learning at SMPN 3 Imogiri, to assess the effectiveness of applying the Civics learning method in increasing students' interest in learning at SMPN 3 Imogiri and To choose alternative Civics learning methods that can be used at SMPN 3 Imogiri to meet the learning needs of students with various interests and talents. The informants in this study were the Principal, PPkn Teachers and Student Representatives of SMPN 3 Imogiri. This study uses a qualitative approach. The research data was obtained through interviews, observation and documentation. The results of this study indicate that applying the PPKn learning method at SMPN 3 Imogiri is proven to be able to improve its students in Civics subjects and is quite effective in increasing students' interest in learning PPKn as well as teaching methods of quizzes, question and answer, power point and discussion for Civics subjects can be an alternative in increasing student learning interest in Civics subjects at SMPN 3 Imogiri.